The design of environmental policy for the olive oil sector in the presence of eco-friendly firms - Gautier, Luis (Elsevier, 2024)
The olive oil sector in the European Union has recently exhibited an increase in the production of eco-friendly olive oil, which is consistent with the policy goals of increasing the production of eco-friendly products and addressing environmental degradation. Under current Common Agricultural Policy (CAP) 2023–2027 regulations, environmental policy in the European Union is predominantly of the command-and-control type with less emphasis on market-based policies. We study the design of environmental policy by comparing an emission tax (market-based policy) and a relative binding standard (command-and-control policy) in an industry where firms are transforming themselves into eco-friendly firms. We argue that an emission tax is a more flexible and efficient policy in this type of industry. Results underscore the role market-based environmental policies can play in promoting the European Union’s policy goals. Additionally, results are applicable to olive oil producers globally, but also other industries transitioning into the production of eco-friendly products.
Keywords: Aceite de oliva - Impuestos; Impuestos ambientales; Product differentiation; Emission tax; Olive oil; Eco-friendly